Driving Sustainable Corporate Tax Compliance in Thailand: The Role of Technology, Responsibility, and Filing Intention in a Hybrid Analytical Framework - Lekjaeng, Suradej; Sincharoonsak, Titaporn (Journal of Posthumanism, 2025)
This study examines the determinants of corporate tax compliance in Thailand, partic-ularly in the context of increasing digitalization. While prior studies have separately addressed technology acceptance and behavioral intention, few have integrated these domains to explain voluntary tax compliance. This research employs a hybrid model that combines the Technology Acceptance Model (TAM), the Theory of Planned Be-havior (TPB), and taxpayer responsibility theory. Using data from 500 corporate ac-countants, we employed Partial Least Squares Structural Equation Modeling (PLS-SEM), Necessary Condition Analysis (NCA), and Importance–Performance Map Analysis (IPMA) to analyze the data. The results demonstrate that perceived ease of use, subjec-tive norms, and perceived behavioral control significantly influence tax intention, which in turn affects compliance behavior. Furthermore, attitudes toward technology and perceived usefulness indirectly support compliance, while taxpayer responsibility ex-hibits a strong direct effect. These findings contribute to the theoretical understanding of compliance behavior and offer practical insights for enhancing technology-enabled tax systems in emerging markets. This study examines the determinants of corporate tax compliance in Thailand, partic-ularly in the context of increasing digitalization. While prior studies have separately addressed technology acceptance and behavioral intention, few have integrated these domains to explain voluntary tax compliance. This research employs a hybrid model that combines the Technology Acceptance Model (TAM), the Theory of Planned Be-havior (TPB), and taxpayer responsibility theory. Using data from 500 corporate ac-countants, we employed Partial Least Squares Structural Equation Modeling (PLS-SEM), Necessary Condition Analysis (NCA), and Importance–Performance Map Analysis (IPMA) to analyze the data. The results demonstrate that perceived ease of use, subjec-tive norms, and perceived behavioral control significantly influence tax intention, which in turn affects compliance behavior. Furthermore, attitudes toward technology and perceived usefulness indirectly support compliance, while taxpayer responsibility ex-hibits a strong direct effect. These findings contribute to the theoretical understanding of compliance behavior and offer practical insights for enhancing technology-enabled tax systems in emerging markets.